3x+7=(5x-4)*2

Simple and best practice solution for 3x+7=(5x-4)*2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+7=(5x-4)*2 equation:


Simplifying
3x + 7 = (5x + -4) * 2

Reorder the terms:
7 + 3x = (5x + -4) * 2

Reorder the terms:
7 + 3x = (-4 + 5x) * 2

Reorder the terms for easier multiplication:
7 + 3x = 2(-4 + 5x)
7 + 3x = (-4 * 2 + 5x * 2)
7 + 3x = (-8 + 10x)

Solving
7 + 3x = -8 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
7 + 3x + -10x = -8 + 10x + -10x

Combine like terms: 3x + -10x = -7x
7 + -7x = -8 + 10x + -10x

Combine like terms: 10x + -10x = 0
7 + -7x = -8 + 0
7 + -7x = -8

Add '-7' to each side of the equation.
7 + -7 + -7x = -8 + -7

Combine like terms: 7 + -7 = 0
0 + -7x = -8 + -7
-7x = -8 + -7

Combine like terms: -8 + -7 = -15
-7x = -15

Divide each side by '-7'.
x = 2.142857143

Simplifying
x = 2.142857143

See similar equations:

| 9+(2/3)x=81 | | -7c(3/4)=65 | | 6-4y=y | | 2a-3=3-4a | | 3a-6=10-a | | (2x-2)2=(3x-2)(x-3) | | 24+2x-x^2= | | 132-6x=2x-20 | | 12x-5=8x-x | | x(p-cv)=cf | | 4t-3=-13-2t | | 5.3+9.2x=7-4x-8.8 | | 1.8x+4.1x=5.7 | | 3.44-1.25=1.05(2.38x+6.81) | | 42x^2+10x=0 | | b=7x(-7) | | -3(2.47+1.25)=9.82 | | b=2x(-3) | | b=-2-4x(-3) | | E=-28+(5-2)*(-4) | | 3x+5=8-7x | | 35.13x-7.26=11-14.91x | | c=-22+(13-5)x(-5) | | y+11=15 | | -22+(13-5)x(-5)= | | 150+x+400=5000 | | 209-6x=30x+21 | | 2000=n(725-420) | | 8r+1=9 | | 4x+14=-19-7x | | 2x(3-x)=5x+7 | | x-2y=-26 |

Equations solver categories